2010
DOI: 10.1007/s00428-010-0993-6
|View full text |Cite
|
Sign up to set email alerts
|

Can nuclear magnetic resonance (NMR) spectroscopy reveal different metabolic signatures for lung tumours?

Abstract: This study aims to evaluate the potential of (1)H NMR spectroscopy, combined with multivariate statistics, for discriminating between tumour and non-involved (control) pulmonary parenchyma and for providing biochemical information on different histological types. Paired tissue samples from 24 primary lung tumours were directly analysed by high-resolution magic angle spinning (HRMAS) (1)H NMR spectroscopy (500 MHz), and their spectral profiles subjected to principal component analysis (PCA) and partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
5
34
1
Order By: Relevance
“…With 1 H high-resolution magic angle spinning (HRMAS) NMR spectroscopy, Duarte et al observed the decreased level of glycine in tumor samples from lung cancer patients, suggesting that glycine might be involved in altered metabolisms in tumor tissues. 23 In our study, we observed specifically altered glycine level in serum samples from BC patients, which is consistent with the results of the previous study.…”
Section: Amino Acids Metabolismsupporting
confidence: 93%
“…With 1 H high-resolution magic angle spinning (HRMAS) NMR spectroscopy, Duarte et al observed the decreased level of glycine in tumor samples from lung cancer patients, suggesting that glycine might be involved in altered metabolisms in tumor tissues. 23 In our study, we observed specifically altered glycine level in serum samples from BC patients, which is consistent with the results of the previous study.…”
Section: Amino Acids Metabolismsupporting
confidence: 93%
“…In fact, we have observed a trend for lipids to be increased in lung tumoral tissue (relative to noninvolved pulmonary parenchyma), 32,33 and although this increase could have multiple sources, including tissue necrosis, its possible relation with the observed changes in the plasma lipoprotein profile should not be ruled out. The poor nutritional status generally associated with cancer has also been reported to account for the reduction in HDL and LDL levels.…”
Section: Articlementioning
confidence: 94%
“…Lactate was found to be increased and glucose was found to be decreased in the plasma of cancer patients, most likely reflecting the well-known increased glycolytic activity of tumor cells (the Warburg effect), as confirmed by metabolic profiling of lung tissues. 32,33,46 Indeed, the standard measurement of glucose in serum samples from 300 fasted patients with a variety of cancer types also showed a significant reduction of glucose levels relative to the same number of gender-and age-matched controls. 44 Consistently with this enhanced glycolysis and as previously reported for leukemia, 47 kidney, 8 liver, 12 and colorectal 18 cancers, the glycolytic product pyruvate was found to be increased.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Model derived features were selected as those with a VIP score >= 1.0. PLSDA is commonly used in metabolomics investigations including multiple forms of cancer, cardiac ischemia, parkinson's disease and asthma (Nishiumi et al, 2010;Bodi et al, 2012;Bogdanov et al, 2008;Carraro et al, 2007;Chen et al, 2011;Duarte et al, 2010;Qiu et al, 2010). This technique has also been previously implemented in our lab investigating hemorrhagic shock (Lexcen, Lusczek, Witowski, Mulier, & Beilman, 2012).…”
Section: Partial Least Squares Discriminant Analysis (Plsda)mentioning
confidence: 99%